PENERAPAN METODE FUZZY MAMDANI UNTUK MEMPREDIKSI JUMLAH PRODUKSI KARET (STUDI KASUS: DATA PERSEDIAAN DAN PERMINTAAN PRODUKSI KARET PADA PTP NUSANTARA XIV (PERSERO) KEBUN AWAYA, TELUK ELPAPUTIH, MALUKU-INDONESIA) - Rahakbauw, D L; Rianekuay, F J; Lesnussa, Y A (JURNAL ILMIAH MATEMATIKA DAN TERAPAN, 2019)
Good corporate management will determine the development of a company. In addition, the necessary production planning is also required to achieve maximum profit. This study uses data from PTP Nusantara XIV (Persero) Awaya Garden, Teluk Elpaputih, Maluku Province Indonesia, which is engaged in the production of raw rubber. This research uses Fuzzy Mamdani method to predict the amount of rubber production based on the demand data, inventory and production of rubber per day in April 2016. From the research result obtained the exact amount of rubber production with the percentage of truth value equal to 87,83% and the resultant error is 12,17%.Keywords : Demand, Fuzzy Logic Mamdani Method, Inventory, Production.